Chronic pain and problematic substance use for veterans during COVID-19: the moderating role of psychological flexibility - Reilly, Erin D.; Wolkowicz, Noah R.; Heapy, Alicia; Ross MacLean, R.; Duarte, Brooke A.; Chamberlin, Elizabeth S.; Harris, J. Irene; Shirk, Steven D.; Kelly, Megan M. (Frontiers in Psychology, 2023)
Background: Chronic pain and problematic substance use are commonly co-occurring and highly detrimental issues that are especially prevalent in U.S. veteran populations. Although COVID-19 made clinical management of these conditions potentially difficult, some research suggests that certain veterans with these conditions did not experience this period as negatively as others. It is thus important to consider whether resilience factors, such as the increasingly-studied process of psychological flexibility, might have led to better outcomes for veterans managing pain and problematic substance use during this time of global crisis. Methods: This planned sub-analysis of a larger cross-sectional, anonymous, and nationally-distributed survey (N = 409) was collected during the first year of the COVID-19 pandemic. Veteran participants completed a short screener and battery of online surveys assessing pain severity and interference, substance use, psychological flexibility, mental health functioning, and pandemic-related quality of life. Results: For veterans with chronic pain and problematic substance use, the pandemic resulted in a significant lowering of their quality of life related to meeting basic needs, emotional health, and physical health compared to veterans with problematic substance use but no chronic pain diagnosis. However, moderation analyses revealed that veterans with these comorbid conditions experienced less negative impacts from the pandemic on quality of life and mental health when they reported greater psychological flexibility. For veterans with problematic substance use only, psychological flexibility was also related to better mental health functioning, but did not significantly correlate with their quality of life. Conclusion: Results highlight how COVID-19 differentially impacted veterans with both problematic substance use and chronic pain, such that this group reported particularly negative impacts of the pandemic on multiple areas of quality of life. However, our findings further emphasize that psychological flexibility, a modifiable resiliency process, also buffered against some of the negative impacts of the pandemic on mental health and quality of life. Given this, future research into the impact of natural crises and healthcare management should investigate how psychological flexibility can be targeted to help increase resiliency for veterans with chronic pain and problematic substance use.